(untitled) (Journal of Governance and Development (JGD), 2022)
This research aims to determine the factors that influence voters using Additional Voter List (AVL) in the election of Samarinda mayor in 2020. This research focuses on the factors that affect voters who have registered in Voter List using suffrage with AVL in Samarinda. Samarinda became a research locus with sampling models in 6 subdistricts and 12 villages. The NVivo 12 Interactive Model analysis and Network Analysis technique used the data analysis. The interactive analysis stage consists of data collection, data reduction, data display, and conclusion. Researchers adopted the Maleong concept to strengthen interactive analysis to analyze the standard degree of truth of research results, therefore data checks must be carried out through credibility, transferability, dependability, and confirmability. The results of this study that the factors that affect AVL include Business (Business), Voting Rights Use Campaign and candidates’ success team, Electronic ID Card Ownership, Continuing Studies, Using Voting Rights, Working Mobility, Moving (Marriage), Domicile Transfer, Data Collection Process, Socialization of Election Stages, Election Implementation Tasks and Moving Citizens. Among the 12 factors, emerge 8 factors have the most substantial influence, namely Moving Domicile, Data Collection Process, Electronic ID Card Ownership, Socialization of Election Stages, Using Voting Rights, Voting Rights Campaign and Candidates’ Success Team, Work Mobility and Moving Citizens.